Finite element simulation of cold upsetting process on AA7075 reinforced with SiC/FA/Gr metal matrix composites. (2021) - Singampalli, Raja Sekhar; Ramji, K.
Abstract: Application of Al-Alloys has been to a great extent in many Industries, since it replaces most of the massive machine parts made of steel and cast iron. Its special characteristic of light weight to strength ratio is more benificial at operating conditions, would lead to greater economy. Favourable mechanical and Tribological characteristics in Al-alloys were not only be achieved by reinforcement composition, but also by means of the process of synthesizing at various conditions. In this context an Aluminiu alloy AA7075 has been reinforced with Silicon carbide, Fly ash and Graphite. Three different composites were fabricated at different weight ratios as 6, 9 and 12% by wieght. Initial composite of AA7075 is formed with 2% of each alloying element and percentage of alloying has been enhanced by one for the rest composites. The entire process of fabrication was accomplished through stircasting method under vortex route. The fabricated copmosites were titled as AA7075-6MMC, AA7075-9MMC and AA7075-12MMC. The main objective of the present work is to investigate the plastic properties of AA7075 and their composites using a renowned finite element analysis tool ANSYS. The results obtained from the simulation process were validated with the analytical one, and found to be in good concurrence. Two different aspect ratios (H/D as 1.0 and H/D as 1.5) are considered for these composites along with the pure AA7075, to analyse the axial, hoop and hydro satatic stresses under the influence of compression. The study reveals that AA7075-9MMC composite exhibited good ductile properties compared to the rest and the base alloy. The Hoop stress value found to be increased to great extent, for the AA7075-9MMC and AA7075-12MMC, compared to rest in the case of aspect ratio 1.5 (H/D), which indicates better plastic characteristics.